Meningkatkan Hasil Belajar IPA dalam Memahami Rangkaian Listrik Seri Melalui Penerapan Metode Eksperimen Pada Siswa Kelas VI SDN 1 Mantang - Irfan, Ahmad Zainul; Najamuddin, M. (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2023)
Abstract : This study aims to improve science learning outcomes in understanding series electrical circuits through the application of experimental methods in grade VI students of SDN 1 Mantang in the odd semester of the 2022/2023 academic year. The method used in this research is the experimental method in class VI students of SDN 1 Mantang. The experimental method is one of the teaching methods that in its presentation is appropriate / suitable to be applied in learning Natural Sciences, because with this method students can develop optimal thinking skills. This class action research was conducted in two cycles on 32 students consisting of 11 male students and 21 female students. After the research was conducted, students’ understanding and learning outcomes of science lessons on series electrical circuits material increased by using experimental methods with an average score of 66 in cycle I to 86.5 in cycle II. In the efforts made by researchers in improving science learning outcomes, it can be concluded that the experimental method is very helpful for teachers in carrying out the learning process, especially when demonstrating with media or materials as a medium for student learning. Keywords: Improvement, Science Learning Outcomes, Experimental Method Abstrak : PenelitianÂ iniÂ bertujuanÂ untukÂ meningkatkanÂ hasilÂ belajarÂ IPAÂ dalamÂ memahamiÂ rangkaian listrikÂ seriÂ melaluiÂ penerapanÂ metodeÂ eksperimenÂ padaÂ siswaÂ kelasÂ VIÂ SDNÂ 1 Mantang semesterÂ ganjilÂ tahunÂ pelajaranÂ 2022/2023.Â MetodeÂ yangÂ digunakanÂ dalamÂ penelitianÂ ini adalah metode eksperimen pada siswa kelas VI SDN 1 Mantang. Metode eksperimen adalah merupakanÂ salahÂ satuÂ metodeÂ mengajarÂ yangÂ dalamÂ penyajiannyaÂ sesuai/cocokÂ untuk diterapkanÂ Â Â dalamÂ pembelajaranÂ IlmuÂ PengetahuanÂ Alam,Â karenaÂ denganÂ metodeÂ iniÂ siswa dapatÂ Â Â mengembangkanÂ kemampuanÂ berfikirÂ secaraÂ optimal.Â PenelitianÂ tindakanÂ kelasÂ ini dilakukanÂ sebanyakÂ duaÂ siklusÂ terhadapÂ 32Â orangÂ siswaÂ yangÂ terdiriÂ dariÂ 11Â siswaÂ laki-laki danÂ 21 siswaÂ perempuan. Setelah penelitian dilakukan, pemahaman dan hasil belajar siswa terhadap pelajaran IPA materi rangkaian listrik seri menjadi meningkat dengan menggunakan metodeÂ eksperimenÂ denganÂ nilaiÂ rata-rataÂ dariÂ 66Â padaÂ siklusÂ IÂ menjadiÂ 86,5 Â padaÂ siklusÂ II. DalamÂ usahaÂ yangÂ dilakukanÂ penelitiÂ dalamÂ meningkatkanÂ hasilÂ belajarÂ IPAÂ dapat disimpulkanÂ bahwaÂ denganÂ metodeÂ eksperimenÂ sangatÂ membantuÂ guruÂ dalamÂ melakukan prosesÂ pembelajaranÂ terutamaÂ saatÂ melakukanÂ peragaanÂ denganÂ mediaÂ atauÂ bahanÂ sebagai media belajar siswa.Â Kata konci: Peningkatan, Hasil Belajar IPA, Metode Eksperimen